FORMATION OF UNITED NATIONS INTERIM FORCE IN LEBANON-II: NEGOTIATING ASPECT (Вісник: Міжнародні відносини, 2021)
The article is devoted to the study of the specifics of the negotiation process in the multilateral (within the framework of the UN Security Council, the European Union) and bilateral (direct parties to the conflict and related parties, the UN and countries that supply contingents to UN peacekeeping operations) formats regarding the formation of the United Nations Interim Force in Lebanon -II (UNIFIL-II) in 2006. Particular attention is paid to the analysis of two approaches to resolving the conflict that arose in connection with the Israeli military operation in 2006 against Hezbollah and accordingly the approach to the formation of peacekeeping forces (regarding their composition, mandate, operational command), which were represented by Israel, the United States, Britain on the one hand, and Lebanon and France on the other. It has been proven that the formation of UNIFIL-II was the result of reaching compromise in the negotiation process.
Keywords: peacekeeping; UN, Lebanon, negotiations